Stress‐associated ectopic differentiation of melanocyte stem cells and ORS amelanotic melanocytes in an ex vivo human hair follicle model. Issue 4 (3rd March 2021) - Rachmin, Inbal; Lee, Ju Hee; Zhang, Bing; Sefton, James; Jung, Inhee; Lee, Young In; Hsu, Ya‐Chieh; Fisher, David E.
Abstract: Hair greying depends on the altered presence and functionality of hair follicle melanocytes. Melanocyte stem cells (MelSCs) reside in the bulge of hair follicles and give rise to migrating and differentiating progeny during the anagen phase. Ageing, genotoxic stress, redox stress and multiple behaviour‐associated acute stressors have been seen to induce hair greying by depleting the MelSC pool, a phenomenon which is accompanied by ectopic pigmentation of these cells, followed by their depletion from the stem cell niche. This aberrant differentiation produces a state from which a return to stem cell‐like quiescence appears to be lost. The cellular features of stress‐induced hair greying have been extensively studied in murine models. Here, we describe a method to assess and quantify human hair follicle MelSC differentiation by measuring ectopically pigmented MelSCs in isolated human hair follicles exposed to specific stress signal mediators. Ionizing radiation, hydrogen peroxide and noradrenaline have been shown to cause hair greying in mice. We demonstrate here that isolated, ex vivo cultured human hair follicles exposed to these treatments display similar ectopic pigmentation within the bulge area which is accompanied by induction of differentiated melanocytic markers. This study suggests that as in murine models, stress signalling induces closely matching phenotypic changes in human hair follicles which can be monitored and studied as a surrogate model for early steps in human hair greying.